PENGARUH REALISASI ANGGARAN PENERIMAAN DAN BELANJA DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PROVINSI NUSA TENGGARA BARAT TAHUN 2017-2022 - Ratih, Diana; Soelistyo, Aris (Program Studi Ekonomi Pembangunan, 2024)
This research aims to examine the influence of the Regional Budget (APBD) on the Gross Regional Domestic Product (GRDP) in West Nusa Tenggara. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) of West Nusa Tenggara and the Directorate General of Budget, Ministry of Finance, from 2017 - 2022 The data analysis technique used regression panel data. The result indicates that Local Own Revenues (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK), and Capital Expenditure (BD) do not have a significant impact on the PDRB in West Nusa Tenggara. However, Revenue Sharing Fund (DBH) has a positive significant influence on the PDRB in West Nusa Tenggara.